1995
DOI: 10.1073/pnas.92.6.2224
|View full text |Cite
|
Sign up to set email alerts
|

The origin recognition complex interacts with a bipartite DNA binding site within yeast replicators.

Abstract: Replicators are genetically defined elements within chromosomes that determine the location of origins of DNA replication. In the yeast Saccharomyces cerevisiae, the ARSI replicator contains multiple functional DNA elements: an essential A element and three important B elements-Bi, B2, and B3. Functionally similar A, Bi, and B2 elements are also present in the ARS307 replicator. Eukaryotic cells duplicate their genetic information for the next generation during the S phase of the cell division cycle. In genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
211
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(218 citation statements)
references
References 26 publications
3
211
0
1
Order By: Relevance
“…We confirmed that this purified ORC was functionally active because it could partially rescue DNA replication in the ORCdepleted, Xenopus egg extracts (data not shown), as shown previously (11). Biotin-labeled, ϳ110-bp dsDNA containing (GGGTT) 8 or a 40-bp AT-rich element was used as a probe for EMSA, and binding specificity was investigated by adding unlabeled competitors into the binding reaction (see Table 1 for their sequences). First, we compared two competitors, AT-rich and (GGGTT) 8 dsDNA (ϳ40 bp) to evaluate the conditions for EMSA.…”
Section: Human Orc Exhibits Sequence Preference For Binding Tomentioning
confidence: 65%
See 3 more Smart Citations
“…We confirmed that this purified ORC was functionally active because it could partially rescue DNA replication in the ORCdepleted, Xenopus egg extracts (data not shown), as shown previously (11). Biotin-labeled, ϳ110-bp dsDNA containing (GGGTT) 8 or a 40-bp AT-rich element was used as a probe for EMSA, and binding specificity was investigated by adding unlabeled competitors into the binding reaction (see Table 1 for their sequences). First, we compared two competitors, AT-rich and (GGGTT) 8 dsDNA (ϳ40 bp) to evaluate the conditions for EMSA.…”
Section: Human Orc Exhibits Sequence Preference For Binding Tomentioning
confidence: 65%
“…(GGGTT) 8 ssDNA, but not (AACCC) 8 ssDNA, inhibited DNA binding of ORC more efficiently than (GGGTT) 8 dsDNA (Fig. 1D); a 10-fold molar excess of (GGGTT) 8 ssDNA almost completely inhibited ORC binding to an AT-rich dsDNA probe, but (GGGTT/CCCAA) 8 dsDNA or (AACCC) 8 ssDNA was less effective. (GGGTT) 8 inhibited as efficiently as AT-rich dsDNA (Fig.…”
Section: Human Orc Exhibits Sequence Preference For Binding Tomentioning
confidence: 99%
See 2 more Smart Citations
“…I n Saccharomyces cerevisiae origins of DNA replication contain conserved A, B1, and B2 elements, where the A element and part of B1 define the binding sequence for the origin recognition complex (ORC) (1)(2)(3). ORC binds to origin DNA in an ATPdependent manner and recruits other essential proteins, such as the initiation factors Cdc6, Cdt1, and the presumptive DNA helicase MCM, to the autonomously replicating sequence (ARS) to form a prereplicative complex (pre-RC) before the initiation of DNA replication that occurs in S phase (4)(5)(6)(7).…”
mentioning
confidence: 99%